Combined impacts of prolonged drought and warming on plant size and foliar chemistry. (30th January 2019) - Orians, Colin M; Schweiger, Rabea; Dukes, Jeffrey S; Scott, Eric R; Müller, Caroline
Abstract: Background and Aims: Future shifts in precipitation regimes and temperature are expected to affect plant traits dramatically. To date, many studies have explored the effects of acute stresses, but few have investigated the consequences of prolonged shifts in climatic conditions on plant growth and chemistry. Methods: Plant size and metabolite profiles were assessed on naturally occurring Plantago lanceolata plants growing under different precipitation (ambient, 50 % less than ambient = drought) and temperature (ambient, +0.8, +2.4 and +4.0 °C above ambient) treatments at the Boston Area Climate Experiment (constructed in 2007). Key Results: The analysis of primary and secondary metabolites revealed pronounced effects of drought, and a precipitation × temperature interaction. Strikingly, the effects of precipitation were minimal at the two lower temperatures but marked at the two higher temperatures. Compared with the ambient condition, plants in the drought plots had lower concentrations of foliar nitrogen, amino acids and most sugars, and higher concentrations of sorbitol, citrate and malate, common stress-induced metabolites. This pattern was especially evident at high temperatures. Moreover, drought-exposed plants showed lower concentrations of catalpol, an iridoid glycoside. Conclusions: While the effect of warming on the metabolite profiles was less pronounced, differences were marked when combined with drought. Given the interactive effect of environmental variables on leaf chemistry, and the fact that woody and herbaceous plants seem to differ in their responses to temperature and precipitation, future studies should account for the direct and indirect effects of the community response to multifactorial field conditions.